2019
DOI: 10.1136/bmjgh-2019-001940
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in the global representation of sites participating in large, multicentre dialysis trials: a systematic review

Abstract: BackgroundThe number of dialysis recipients is growing worldwide, making it important that the full range of patient populations are represented in randomised trials. As trial recruitment has not previously been examined at a global level, we compared the location of trial sites recruiting to large multicentre randomised controlled trials (RCTs) in dialysis to the global distribution of dialysis recipients.MethodsA systematic review (2007–2016) was conducted to identify RCTs enrolling ≥100 dialysis patients fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…This lack of discussion within previous analyses is surprising given the established literature illustrating that participants recruited to trials testing hemodialysis interventions may not reflect the broader clinical population from which they are drawn 38,39 and broader inequities in hemodialysis care. [40][41][42] Notably, patients enrolled in hemodialysis trials have also been found to be younger and have fewer comorbidities than patients in the clinical setting, 43 with many trials systematically excluding patients above the age of 65.…”
Section: Discussionmentioning
confidence: 98%
“…This lack of discussion within previous analyses is surprising given the established literature illustrating that participants recruited to trials testing hemodialysis interventions may not reflect the broader clinical population from which they are drawn 38,39 and broader inequities in hemodialysis care. [40][41][42] Notably, patients enrolled in hemodialysis trials have also been found to be younger and have fewer comorbidities than patients in the clinical setting, 43 with many trials systematically excluding patients above the age of 65.…”
Section: Discussionmentioning
confidence: 98%
“…19 Such selection bias favoring "healthy patients" is not unique to dialysis-related clinical trials-entirely concordant findings are seen in clinical trials within other medical subspecialties. [20][21][22][23][24][25][26] However, to illustrate the impact of this situation in the real world, an exercise can be undertaken using the dialysis registry data from New Zealand from As importantly, what is the optimal approach for hemodialysis providers? The overall picture suggests that they should not be continuing to decrease default dialysate [Na + ] without further evidence or assessment for benefit and harm.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate in the studies was approximately half of that in the registry data to which it was compared (8.9 versus 18.6 deaths per 100 patient years) 19 . Such selection bias favoring “healthy patients” is not unique to dialysis‐related clinical trials—entirely concordant findings are seen in clinical trials within other medical subspecialties 20‐26 . However, to illustrate the impact of this situation in the real world, an exercise can be undertaken using the dialysis registry data from New Zealand from 1 January 1998 to 31 December 2017.…”
Section: Discussionmentioning
confidence: 99%
“…This is encouraging for the scientific research community since any untoward events can be monitored and rectified before widespread use leads to uncontrollable cascades. However, research representation in sample subsets is far from equitable (Algahtani et al 2018;Samalik et al 2022;Smyth et al 2019). The thalidomide tragedy needs no revisiting (Kim and Scialli 2011) and with the availability of preprint sites, virtual conferences and other collaborative mediums that permit the rapid dissemination of research findings, having equitable representation amongst patient populations before drawing research conclusions is more feasible than before.…”
Section: A Accounting For Variations In Population Effectsmentioning
confidence: 99%